2015
DOI: 10.1177/1077801215576579
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Administration of Sexual Assault Prevention and Risk Reduction Programming

Abstract: The present study describes the 4- and 7-month postintervention outcomes of a sexual assault risk reduction program for women, which was part of an evaluation that included a prevention program for men. Relative to the control group, participants evidenced more relational sexual assertiveness and self-protective behavior, and were more likely to indicate that they utilized active verbal and physical self-defense strategies. Whether or not women experienced subsequent victimization did not differ between groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 39 publications
3
54
1
Order By: Relevance
“…Note, however, that other studies with self-defense components did not report such findings [41,[48][49][50]. Also note that this study (Hollander) is not without flaws.…”
Section: Acta Psychopathologica Issn 2469-6676contrasting
confidence: 46%
“…Note, however, that other studies with self-defense components did not report such findings [41,[48][49][50]. Also note that this study (Hollander) is not without flaws.…”
Section: Acta Psychopathologica Issn 2469-6676contrasting
confidence: 46%
“…Data were garnered from a larger study examining the effectiveness of sexual assault prevention programming for college students living in primarily freshmen residence halls Gidycz, Orchowski, & Berkowitz, 2011; Gidycz, Orchowski, Probst, et al, 2015). The present study utilized only the responses from women randomly assigned to the control group.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to reducing the risk of assault, self‐defense training has other benefits to women that extend far beyond the moment of assault. Multiple studies have found that women who learn self‐defense report greatly increased self‐defense self‐efficacy , or the confidence that one could defend oneself effectively if assaulted (David, Simpson, & Cotton, ; Gidycz et al, ; Hollander, , , ; Jordan & Mossman, ; Kidder, Boell, & Moyer, ; McDaniel, ; Orchowski et al, ; Ozer & Bandura, ; Pinciotti & Orcutt, ; Senn, ; Senn et al, ; Senn, Gee, & Thake, ; Weitlauf, Cervone, Smith, & Wright, ; Weitlauf, Smith, & Cervone, ). Self‐efficacy is a major predictor of actual effectiveness (Bandura, , ) and is linked to a range of positive psychological and behavioral outcomes (Pinciotti & Orcutt, ), including assertive responses to sexual assault (Nurius, Norris, Graham, & Gaylord, ).…”
Section: Are There Other Consequences Of Self‐defense Training?mentioning
confidence: 99%
“…Self‐defense students report decreased symptoms of anxiety and depression (Brecklin, ; Ozer & Bandura, ). Survivors who have taken self‐defense classes also report decreases in PTSD symptoms (David et al, ), as well as reductions in self‐blame for past assaults (Brecklin & Ullman, ; Gidycz et al, ; Gidycz, Rich, Orchowski, King, & Miller, ; Senn, Hobden, & Eliasziw, ) as they come to understand the dynamics of assault and attribute more responsibility to perpetrators rather than to victims (Gidycz et al, ; Gidycz et al, , ; Senn et al, ; Senn et al, ; Senn et al, ; Senn, Saunders, & Gee, ). Reducing self‐blame may decrease vulnerability to future assaults, because self‐blame impedes assertive resistance (Nurius et al, , ).…”
Section: Are There Other Consequences Of Self‐defense Training?mentioning
confidence: 99%
See 1 more Smart Citation